The significance of connective tissue dysplasia in the development of cervical incompetence - L. I. Kokh; L. P. Nazarenko; J. V. Tsukanova; I. V. Satysheva (Бюллетень сибирской медицины)
100 pregnancy women at 13—30 weeks gestations were examined to study significance of connective tissue dysplasia in the development of cervical incompetence. Data of objective examination, anamnesis, physical examination. The role of connective tissue dysplasia was firmed by presence its markers, loss of weight, diseases with connective tissue dysplasia.